2008
DOI: 10.1038/gene.2008.72
|View full text |Cite
|
Sign up to set email alerts
|

The IL-10R1 S138G loss-of-function allele and ulcerative colitis

Abstract: Genetic predisposition is a risk factor for the development of inflammatory bowel diseases (IBDs). Disruption of the interleukin (IL)-10 pathway in mice causes intestinal inflammation similar to human IBD. Two common non-synonymous IL-10R1 variants, S138G and G330R, were cloned and expressed in HeLa and Ba/F3. A reduction in IL-10-induced STAT1 and STAT3 activation was seen for IL-10R1-S138G (but not IL-10R1-G330R) by phosphospecific western blotting in both cell types. When analyzing 52 world populations for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 33 publications
2
35
0
Order By: Relevance
“…20,21 These data suggested that the variant (p.G330R) did not affect the signaling events upstream to STAT3 activation including IL-10 binding and IL-10R1 activation, but other mechanisms contributed to the dysfunction of this variant. Herein, we found that the novel compound heterozygous mutations (p.T84I and p.R101W) abrogated IL-10R1 activation and led to impaired IL-10R function.…”
Section: Il-10r1 Mutations Impair Il-10 Signalingmentioning
confidence: 84%
See 1 more Smart Citation
“…20,21 These data suggested that the variant (p.G330R) did not affect the signaling events upstream to STAT3 activation including IL-10 binding and IL-10R1 activation, but other mechanisms contributed to the dysfunction of this variant. Herein, we found that the novel compound heterozygous mutations (p.T84I and p.R101W) abrogated IL-10R1 activation and led to impaired IL-10R function.…”
Section: Il-10r1 Mutations Impair Il-10 Signalingmentioning
confidence: 84%
“…23 The correlation of a SNP of IL-10R1 with IBD was demonstrated in some ethnic populations but not in others. 21,24 Therefore, besides the discovery in European and Lebanese, 13,14 it is useful to examine the rare variants of IL-10R in neonatal-onset IBD in other populations. In this study we further identified such rare variant in the Han Chinese.…”
Section: Il-10r1 Mutations Impair Il-10 Signalingmentioning
confidence: 99%
“…Nevertheless, correlations between certain haplotypes of the IL-10 and IL-10R1 genes and the occurrence and/or course of various diseases were described (230)(231)(232)(233)(234)(235). In fact, in Lupus erythematosus, not only was the correlation statistically significant between the haplotype and the occurrence of disease, but also between the type of antibody and the severity of the clinical condition (230,232,236).…”
Section: Role Of Il-10 In Immune-mediated Diseasesmentioning
confidence: 99%
“…Recently, IL10R mutations causing functional impairment of IL10 signaling were implicated in early-onset enterocolitis (5). Also, the S138G variant of IL10R1 was linked to ulcerative colitis (6). This IL10R2 variant likely represents an adaptive change in the human genome as it reduces the ability of cmvIL10 to utilize the host's IL10 signaling pathway (7).…”
Section: Introductionmentioning
confidence: 99%